2021
DOI: 10.1108/jima-10-2020-0329
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring the halal integrity of the food supply chain through halal suppliers: a bibliometric review

Abstract: Purpose This paper aims to provide a brief bibliometric review of previous literature reviews in understanding halal suppliers in the food supply chain to achieve halal standards from upstream to downstream. Design/methodology/approach The method used was a structured literature review sample of during 2008–2020 totalling 142 articles. The authors use the R-package bibliometric and VOSviewer to find out information about journals, articles, authors, citations, keywords and word hierarchy maps. Findings The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 73 publications
(109 reference statements)
0
16
0
Order By: Relevance
“…Another research was written by Handayani et al (2021). Their work aims to present a concise bibliometric analysis of previous literature reviews on halal producers in the food supply chain to attain halal standards from upstream to downstream.…”
Section: Halal Supply Chain Literaturementioning
confidence: 99%
“…Another research was written by Handayani et al (2021). Their work aims to present a concise bibliometric analysis of previous literature reviews on halal producers in the food supply chain to attain halal standards from upstream to downstream.…”
Section: Halal Supply Chain Literaturementioning
confidence: 99%
“…To explain the relationship between food safety and HF, Wahyuni, et al (2019) conducted a bibliometric analysis and identified the impactful studies, scholars, and universities contributing to the HF field. Recently, Handayani, et al (2021) aimed to comprehend halal suppliers in the food supply chain to achieve halal standards from upstream to downstream, employing a bibliometric analysis.…”
Section: Main Review Studies On Hfmentioning
confidence: 99%
“…Recently, Handayani et al (2021) aimed to comprehend halal suppliers in the food supply chain to achieve halal standards from upstream to downstream, using a bibliometric analysis.…”
Section: Knowledge Diffusion Of Halal Food Researchmentioning
confidence: 99%
“…These countries have a high demand for halal products and adopted halal logistics for maintaining halal integrity from farm to fork. Handayani et al (2021) conducted a bibliometric analysis for the Halal domain and shows that halal logistics is a significant research area that needs to be focussed. Further, the demand for halal logistics is also increased to maintain halal integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Handayani et al (2021) conducted a bibliometric analysis for the Halal domain and shows that halal logistics is a significant research area that needs to be focussed. Further, the demand for halal logistics is also increased to maintain halal integrity.…”
Section: Introductionmentioning
confidence: 99%